Ethical Conflicts in Care Throughout the Life Cycle in Primary Care in Chile: Perspectives of an Ethics Committee - Campillay, Maggie; Nadal, Carmen (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
People-centred health care recognizes patients as subjects of rights, while the principle of continuity of care is related to longitudinality, establishing a long-term therapeutic relationship throughout the individual life cycle. These principles of the comprehensive care model in Chile pose ethical challenges to primary health care teams. The purpose of this article is to describe and analyze the main ethical conflicts deliberated by a primary care clinical ethics committee, differentiated by life cycle. A qualitative methodology was used, with a case study approach reviewing 30 of the 70 queries received by the committee over a period of seven years. The results show that ethical conflicts during adolescence and in the care of elderly people generate greater difficulties for the health team. The main conclusions are related to the responsibility of addressing them appropriately, and for contributing to comprehensive care plans that always consider the ethical aspects of care.